Pendampingan Penyusunan E-Modul dengan Pendekatan Saintifik Berbasis FlipBook Maker - Yandi Heryandi; Herani Tri Lestiana (Dimasejati: Jurnal Pengabdian Kepada Masyarakat, 2024)
ASSİSTANCE İN PREPARİNG FLIPBOOK MAKER-BASED E-MODULES WİTH A SCİENTİFİC APPROACH. Technological advances require educators to be more creative and innovativein developing teaching materials with a scientific approachlearner-centered. However, teaching materials that are often used inIntegrated Islamic School is a textbook that only contains materialdiscussion. The aim of this service is to provide assistancepreparation of e-modules based on Flipbook Maker with a scientific approach,namely: (1) to determine the teacher's understanding of the preparation of e-modulesbased on Flipbook Maker with a scientific before and after approachmentoring activities; (2) to find out the teacher's response toassistance activities in the preparation and use of e-based modulesFlipbook Maker with a scientific approach. Participants of the activity is teachers of all subjects in SMP IT Al Falah Cirebon. This community service was carried out in two major activities, namely In Service Training (IST) and On the Job Training (OJT). This service shows that: (1) There has been a significant increaseon teacher understanding regarding Flipbook-based learning e-modulesMaker with a scientific approach. Average level of teacher understandingbefore participating in training and mentoring activities is 56%in the poor category. After participating in training activities andmentoring, the average level of teacher understanding increased to 94%with the very good category. (2) Based on the related response questionnaireservice activities carried out, participants gave positive responsesvery good in terms of material content, material presentation, and mentoringpreparation of e-modules, with an average percentage of 95%.